Introduction to programming in Java : an interdisciplinary approach - Sedgewick, Robert, 1946- (Addison-Wesley, 2017)
Programming skills are indispensable in today's world, not just for computer science students, but also for anyone in any scientific or technical discipline. Introduction to Programming in Java, Second Edition, by Robert Sedgewick and Kevin Wayne is an accessible, interdisciplinary treatment that emphasizes important and engaging applications, not toy problems. The authors supply the tools needed for students and professionals to learn that programming is a natural, satisfying, and creative experience, and to become conversant with one of the world's most widely used languages. --